Analytic Network Process Decision Making Algorithm - Zeeshan, Asim; Sorooshian, Shahryar (Pushpa Publishing House, 2016)
To identify an accurate decision model with a number of distinctive criteria and alternatives are considered to be difficult and complex. In this case, analytic network process (ANP) becomes a significant instrument with a character of accuracy among other complicated models which use a number of criteria with complex feedback interrelation. This paper aims at to present a comprehensive description of multi-criteria decision making techniques with a significant feature of ANP, which is considered as a more robust approach than AHP. The paper offers a brief analysis regarding the ANP methodology in complex multi-criteria decision making, and highlights some recommendations.